2014
DOI: 10.1039/c4ra09548k
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted layer-by-layer electrospun membranes: antibacterial and antioxidative applications

Abstract: Layer-by-layer assembled films have been exploited for functional materials. Tannic acid with previously confirmed antibacterial and antioxidant potentials was deposited on cellulose nanofibrous mats. The LbL assembly technique allowed sufficient binding of TA and AgNPs-Lys to the supporting substrate via hydrogen bond and electrostatic interactions. The properties and morphology of the AgNPs-Lys/TA multilayer assembly membranes were characterized by X-ray photoelectron spectroscopy (XPS), Fourier transform in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…In the infrared spectra, a characterization peak was in the range of 3200-3400 cm - indicating the electrostatic interactions between zein and TA. The peak at 1204 cm -1 is associated with HO-C in plane bend of hydroxyl group in TA [34]. Seen from the FTIR spectrum of zein-TA/Fe III NPs and zein-TA/Cu II NPs, the reduced intensity of the HO-C stretching peak also indicated that the phenolic groups coordinated with metal ions peak when compared with the spectrum of the zein-TA sample and TA [30].…”
Section: Characterization Of Metal-ta Coated Zein Npsmentioning
confidence: 83%
See 1 more Smart Citation
“…In the infrared spectra, a characterization peak was in the range of 3200-3400 cm - indicating the electrostatic interactions between zein and TA. The peak at 1204 cm -1 is associated with HO-C in plane bend of hydroxyl group in TA [34]. Seen from the FTIR spectrum of zein-TA/Fe III NPs and zein-TA/Cu II NPs, the reduced intensity of the HO-C stretching peak also indicated that the phenolic groups coordinated with metal ions peak when compared with the spectrum of the zein-TA sample and TA [30].…”
Section: Characterization Of Metal-ta Coated Zein Npsmentioning
confidence: 83%
“…In addition, the C/O ratio of zein, zein-TA/ Fe III and zein-TA/Cu II were obtained to be 4.12, 2.04 and 2.38, respectively (Table S1). As is well-known, TA was rich in oxygen, 43.27%, much higher than in zein which also certified the metal-phenolic films coating on zein NPs [34].…”
Section: Characterization Of Metal-ta Coated Zein Npsmentioning
confidence: 98%
“…26,27 For the LBL coated lms, the observed increase in intensity of the absorption band at 1716 and 1615 cm À1 as shoulders of the amide I or -OH bending was due to the carbonyl CO vibration of the TA ester bond and C]C stretching vibrations of aromatic ring, respectively. 17 In addition, compared with the spectrum of cellulose nanobers, the presence of the peak located at 1540 cm À1 and accompanied with a shoulder peak was attributed to the N-H vibrations and C]C stretching vibrations, respectively (Fig. 2a-d).…”
Section: Surface Morphology Analysis Of Lys/ta Nanobrous Membranesmentioning
confidence: 95%
“…TA has been used in electrospinning with polycaprolactone [18], to coat cellulose nanofibers [19] and as a crosslinker for chitosan fibers [20] for potential use in biomedical, pharmaceutical and food applications. As DOPA, TA shows a great binding affinity for metal ions [21] and for many polymers including polyvinyl alcohol (PVA) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Tannic acid (TA) is a water-soluble, plant polyphenol with natural antioxidant, antimicrobial, and antiviral activities which has interest for practical applications across many different fields [ 13 , 14 , 15 , 16 , 17 ]. TA has been used in electrospinning with polycaprolactone [ 18 ], to coat cellulose nanofibers [ 19 ] and as a crosslinker for chitosan fibers [ 20 ] for potential use in biomedical, pharmaceutical and food applications. As DOPA, TA shows a great binding affinity for metal ions [ 21 ] and for many polymers including polyvinyl alcohol (PVA) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%